1960
DOI: 10.1073/pnas.46.12.1576
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the Dinitrophenol-Sensitive Atp-Adp Exchange Reaction of Oxidative Phosphorylation

Abstract: Intact rat liver mitochondrial as well as fragments of mitochondrial membranes capable of oxidative phosphorylation2 catalyze an exchange reaction between ATP and ADP which is inhibited by 2,4-dinitrophenol (DNP). The exchange enzyme has been postulated to catalyze the terminal reaction of oxidative phosphorylation by which ATP is formed.'-5 The ATP-ADP exchange reaction is inhibited by dinitrophenol only in freshly prepared particles capable of phosphorylation; aging of the particles causes no loss of activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
1970
1970

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This results in the observed decrease in Vmax through a decrease in turnover which is directly proportional to the rate of electron flow. Azide also inhibits the ATP-P1 exchange reaction of oxidative phosphorylation (reactions b & c) but the ATP-ADP exchange (reaction c) is relatively insensitive (22,23 (21) found that ammonia inhibits the oxidation of DPNH in beet root mitochondria. They suggest that this is the mechanism of the inhibition of respiration by ammonia in intact plants.…”
Section: Methodsmentioning
confidence: 99%
“…This results in the observed decrease in Vmax through a decrease in turnover which is directly proportional to the rate of electron flow. Azide also inhibits the ATP-P1 exchange reaction of oxidative phosphorylation (reactions b & c) but the ATP-ADP exchange (reaction c) is relatively insensitive (22,23 (21) found that ammonia inhibits the oxidation of DPNH in beet root mitochondria. They suggest that this is the mechanism of the inhibition of respiration by ammonia in intact plants.…”
Section: Methodsmentioning
confidence: 99%